2022
DOI: 10.3390/met12071103
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate and Temperature Effects on Formability and Microstructure of AZ31B Magnesium Alloy Sheet

Abstract: Magnesium alloys play an important role in lightweight structures, which are extensively used in different industries due to their excellent mechanical and physical properties. In this paper, the formability of the AZ31B magnesium alloy sheet was studied by using tensile tests at different temperatures (from 25 to 250 °C) and strain rates (from 0.017 s−1 to 0.34 s−1). The results showed that the material behaves with positive temperature sensitivity when forming at a temperature lower than 200 °C. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The maximum texture intensity was 54.83 and 50.62 MUD at a pulse current of 0 and 100 A, respectively; the texture intensity decreased significantly, which were 21.01 and 19.84 MUD at a pulse current of 200 and 300 A, respectively. Li et al [39] and Wu et al [40] found that when the temperature exceeded 350 °C, the stress-strain curves of AZ31 and AZ61 Mg alloys show a large steady-state region, which promoted complete dynamic recrystallisation. Because of the low stacking fault energy of magnesium alloys, dynamic recrystallisation readily occurred during the thermal deformation and resulting in more randomised texture distribution.…”
Section: Effect Of Pulse Current On Texturementioning
confidence: 99%
“…The maximum texture intensity was 54.83 and 50.62 MUD at a pulse current of 0 and 100 A, respectively; the texture intensity decreased significantly, which were 21.01 and 19.84 MUD at a pulse current of 200 and 300 A, respectively. Li et al [39] and Wu et al [40] found that when the temperature exceeded 350 °C, the stress-strain curves of AZ31 and AZ61 Mg alloys show a large steady-state region, which promoted complete dynamic recrystallisation. Because of the low stacking fault energy of magnesium alloys, dynamic recrystallisation readily occurred during the thermal deformation and resulting in more randomised texture distribution.…”
Section: Effect Of Pulse Current On Texturementioning
confidence: 99%